2022
DOI: 10.3390/dj10120237
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Polyetheretherketone (PEEK) as an Alternative Post and Core Material: Five-Year Follow-Up Report

Abstract: This clinical report demonstrated the use of polyetheretherketone (PEEK) for manufacturing of custom-made post and core in weakened endodontically treated central incisors. The PEEK structure was manufactured using computer-aided design/computer-aided manufacturing (CAD/CAM). The optimal fit of this custom-made endodontic post allowed a thinner cement layer; and removed the need to manufacture a core build-up. While supplementary clinical trials and in vitro studies are needed to totally elucidate the advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A couple of clinical cases [41,42] restoring maxillary incisors with custom-made PEEK post-core supporting single-unit lithium disilicate ceramic crowns, are present in the literature. In both of them, a ferrule of at least 2 mm was present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of clinical cases [41,42] restoring maxillary incisors with custom-made PEEK post-core supporting single-unit lithium disilicate ceramic crowns, are present in the literature. In both of them, a ferrule of at least 2 mm was present.…”
Section: Discussionmentioning
confidence: 99%
“…In both of them, a ferrule of at least 2 mm was present. In the 5-year follow-up report [41], debonding was not observed and PEEK was considered to be an appropriate material to successfully restore central incisors. Another report, with a 3-year follow-up, concluded that PEEK can be a viable alternative for post materials.…”
Section: Discussionmentioning
confidence: 99%
“…All of the test specimens in this investigation showed load-bearing values greater than 1000 N, which suggests that they have sufficient fracture strength to withstand physiological occlusal stresses [33] . Significantly, three-unit PEEK FDP copings showed plastic deformation at 1200 N and fracture loading at 1378 N, according to Stawarczyk et al [3] . Notwithstanding the encouraging outcomes, it is critical to recognize constraints.…”
Section: Peek Applications In Dental Prosthesesmentioning
confidence: 90%
“…Compared to Co-Cr or titanium, PEEK is easier to mill and polish, making it a more favourable material to utilize in CAD-CAM milling. This results in prostheses that are lightweight and non-allergic [2,3] . Studies show that PEEK fixed dentures machined using CAD-CAM technology have better fracture resistance than dentures made of zirconia, alumina, or lithium disilicate glass-ceramic [1] .…”
Section: Advantages Of Cad-cam Milling With Peekmentioning
confidence: 99%
See 1 more Smart Citation